Ginger root powder enhanced the growth productivity, digestibility, and antioxidative capacity to cope with the impacts of heat stress in rabbits. (August 2021) - Amber, Khairy; Badawy, Neamt A.; El-Sayd, Abd El-Naem A.; Morsy, Wael A.; Hassan, Aziza M.; Dawood, Mahmoud A.O.
Abstract: Heat stress is the most significant environmental factor involved in the impairment of the health status of rabbits and lowering their productivity. Using medicinal feed additives is suggested to relieve heat stress-induced oxidative stress in rabbits. The study investigated the possible protective role of ginger root ( Zingiber officinale ) against heat stress in rabbits. Five week old rabbits were assigned randomly into four groups (48 rabbits each) and fed a basal diet supplemented with 0, 2.5, 5.0, and 7.5 g ginger powder/kg diet. The temperature and relative humidity inside the rabbitry units were kept at 33.0 ± 5.5 °C and 74.5 ± 4.5%, respectively, during 8 weeks fattening period. The results showed that rabbits that received the 7.5 g ginger powder/kg supplement had the highest final body weight. Rabbits that received different ginger powder levels recorded lower mortality values during the experimental period compared to that received the control diet, but the differences were not significant (5.0 vs. 10.0%, respectively). Rabbits fed 5.0 and 7.5 g ginger diet recorded the best food conversion ratio ( P  < 0.001). The weight of the carcass was significantly increased ( P  < 0.01) by supplementing ginger powder in diets. The digestibility of dry matter, organic matter, crude protein, and nitrogen free extracts nutrients was increased, but ether extract was significantly decreased ( P  < 0.001) by using ginger powder in diets. The detected blood metabolites displayed increased total protein but decreased triglycerides, total cholesterol, high-density lipoprotein (HDL), and low-density lipoprotein (LDL) in rabbits treated with ginger. Rabbits fed 5.0 and 7.5 g ginger powder had the highest plasma total antioxidative capacity (TAC) and the lowest ( P  < 0.01) plasma malondialdehyde (MDA) concentration compared to those fed control diet. Conclusively, supplementing ginger powder up to a 5.0 g/kg diet for growing rabbits is recommended to improve the growth performance and enhanced viability under heat stress conditions. Highlights: We investigated the possible protective role of ginger root against heat stress in rabbits. Rabbits received a 7.5 g ginger powder/kg diet had the highest final body weight. Rabbits that received different ginger powder supplements recorded lower mortality values. The digestibility of nutrients was increased by using ginger powder in diets. Rabbits that were fed ginger powder and grown under high stress had increased plasma TAC and lower plasma MDA concentrations.